2012
DOI: 10.1016/j.crci.2012.05.020
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization and catalytic activity studies on cordierite honeycomb coated with ZrO2 based solid super acids

Abstract: Cordierite honeycomb coated with solid acids such as ZrO 2 , Mo/ZrO 2 and W/ZrO 2 were synthesized. These solid acid catalysts were also synthesized in their powder forms. The catalytic materials were characterized for their physicochemical properties such as surface area, surface acidity, crystallinity and morphology by using techniques such as BET, NH 3 -TPD/n-butylamine back titration, powder XRD and SEM respectively. The catalytic activity of these catalytic materials was determined in an acid catalyzed tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…The reaction mixture was refluxed at refluxing temperature (~65 °C) for 2 h. After a stipulated reaction period (2 h) the hot reaction mixture was filtered to separate the HC catalyst. The %FFA was measured by determining its acid value by following an acid-base titration method as described elsewhere [24].…”
Section: Production Of Biodieselmentioning
confidence: 99%
“…The reaction mixture was refluxed at refluxing temperature (~65 °C) for 2 h. After a stipulated reaction period (2 h) the hot reaction mixture was filtered to separate the HC catalyst. The %FFA was measured by determining its acid value by following an acid-base titration method as described elsewhere [24].…”
Section: Production Of Biodieselmentioning
confidence: 99%
“…The total surface acidity (TSA) values of ZrO 2 and 6% MZ (both in HC coated and powder forms) are given in Table 1. Zirconia was found to be less acidic when compared to 6% MZ indicating that the incorporation of Mo (VI) ions increases the number of acid sites on zirconia thereby increasing the TSA values of 6% MZ [9].…”
Section: Resultsmentioning
confidence: 97%
“…The broad band at 824 cm -1 were shown that the Mo-O-MO stretching mode of vibration for MoO 3 . The band at about 1638 cm -1 attributed acidic hydroxyl proton and about 3421 cm -1 stretching mode of hydrogen bonding exists in all the catalysts [33,34].…”
Section: Resultsmentioning
confidence: 99%